﻿Rediscovery of a lost semi-aquatic Leaf Beetle in the Hula Valley, Israel (Coleoptera, Chrysomelidae, Donaciinae) - David G. Furth; Matteo Montagna; Giulia Magoga (ZooKeys, 2023)
Between 1951–1958, most of the Hula Lake and its surrounding swamps in the Upper Jordan River (Rift) Valley of Israel were drained with the supposed purposes to eliminate malaria and to reclaim land for agriculture; both reasons later proved to be unnecessary decisions. With the paucity of biological knowledge of the Hula region, especially its aquatic invertebrates, accurate assessment of the environmental damage from this drainage is still being realized. Based on natural history museum collection specimen records, the pre-drainage presence of some aquatic insect species has been verified. Among these was Donacia bicolora, a member of a semi-aquatic subfamily (Donaciinae) of Leaf Beetles (Chrysomelidae) and whose Israeli populations were thought to have gone extinct because of the drainage of the Hula and other locations. Recently this species was rediscovered in two populations. However, the molecular identification of two of these recently collected specimens from one population revealed that the identity of this species is actually Donacia simplex. In this work, the re-discovery of this species is detailed, and its conservation importance discussed.